청소년의 돈을 딴 경험과 도박 유해환경이 문제도박에 미치는 영향: 성별 비교를 중심으로 - 이래혁; 장혜림; 이재경; Lee, RaeHyuck; Chang, Hae-Lim; Lee, Jaekyoung (한국콘텐츠학회 논문지, 18(9), 2018)
This study aimed to examine the influences of winning money from betting games and gambling environments on problem gambling among adolescents in South Korea, with particular attention to gender differences in the influences. This study performed a series of regression analyses by using a sample of 14,008 adolescents from the 2015 Survey on Youth Gambling Problems. The findings are as follows. First, winning money from betting games was associated with higher likelihood of doing problem gambling among adolescents. Second, living in a neighborhood with gamblers or gambling places was associated with higher likelihood of doing problem gambling among adolescents. Third, the influence of winning money from betting games on problem gambling was more pronounced for male adolescents. Fourth, there were no gender differences in the influence of living in a neighborhood with gamblers or gambling places on problem gambling. Based on the findings, implications for addressing problem gambling among adolescents were discussed. 본 연구는 청소년의 돈을 딴 경험과 도박 유해환경 노출이 문제도박에 미치는 영향 및 성별 차이 분석을 목적으로 수행되었다. 이를 위해 2015년 청소년 도박문제실태조사에 참여한 14,008명을 대상으로 분석을 실시하였다. 주요 결과는 다음과 같다. 첫째, 청소년의 돈을 딴 경험은 문제도박에 정적으로 유의미한 영향을 미쳤다. 둘째, 청소년의 주변에 도박자가 있는 경우나 도박장이 있는 경우 모두 문제도박에 정적으로 유의미한 영향을 미치는 것으로 분석되었다. 셋째, 성별로 구분해보면, 돈을 딴 경험이 문제도박에 미치는 영향은 남학생에게서 더 두드러지는 것으로 나타났다. 넷째, 주변에 도박자나 도박장이 있는 것이 문제도박에 미치는 영향에서는 성별 차이가 나타나지 않았다. 이상과 같은 결과를 바탕으로 청소년의 문제도박에 대처하기 위한 실천적 정책적 방안을 논의하였다.